Design and control of high-power density converters with power factor correction using multilevel rectifiers - Prakash A. Kharade; J. Jeyavel; Nitin R. Ingale; Shashikant D. Jadhav (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
High-power density converters are critical in modern electrical systems, particularly in applications requiring efficient power conversion and high performance, such as industrial drives, renewable energy systems, and electric vehicles. The majority of active-controlled AC/DC converters are built using the boost converter technique. This technique offers a high input Power Factor (PF), which lowers total harmonic distortion and circuit power losses while increasing conversion efficiency. The objective of the research was to investigate the optimal methods for designing and producing PFCs with high power densities and to assess the effectiveness of both topologies through simulation and experimental testing. The work focuses on designing and controlling high-power density converters with power factor correction using multilevel rectifiers. It aims to enhance efficiency, reduce harmonic distortion, improve power quality, and optimize performance in high-power applications through advanced converter topologies and control strategies. In classic boost converter-based PFC systems, the input filter inductor of the boost converter's size and the bank of twice-line frequency energy buffering capacitors (TLFEB) are two of the main obstacles to obtaining high power density. Accordingly, the article suggested multilevel inverters for high power density. Initially, the study proposed the three-phase dual boost five-level rectifier to improve core coupled inductors. The paper also introduces a six-level Flying Capacitor Multilevel (FCML) boost converter-based Power Factor Correction (PFC) front end. Due to the FCML converter's unique properties, the filter inductor's size may be drastically reduced while keeping high efficiency, thus enhancing the PFC front end's power density. By using a single-phase cascaded H-bridge inverter to optimise the boost converter voltage and current parameters, the performance of both PFC topologies was examined. The combination of high-energy-density ceramic capacitors and a single-phase cascaded H-bridge seven-level inverter converter can significantly enhance the performance of the three-phase rectifier. The multilevel converter's dynamics have been analysed and implemented using Matlab software. For universal AC input, 1.5 kW power rating, and 400-V DC output, a hardware prototype is created. The hardware prototype shows increased efficiency and power density in comparison to existing methods while maintaining a high PF and minimal THD.